Penggunaan Media Pembelajaran Berbasis Canva dan Wordwall Dalam Meningkatkan Hasil Belajar IPS pada Murid Kelas VI UPT SD Negeri 74 Bontorita II Kabupaten Takalar - Rahmiwati, Rahmiwati; AS, Husain; Rahman, Nawir (CV. Rayyan Dwi Bharata, 2025)
This research is a classroom action research that aims to improve social studies learning outcomes through the use of Canva and Wordwall-based learning media in grade VI students of SD Negeri 74 Bontorita II, Takalar Regency. The subject of this study is grade VI students of SD Negeri 74 Bontorita II, Takalar Regency with a total of 21 students, consisting of 14 boys and 7 girls. This research was carried out in two cycles, namely cycle I which was carried out 3 meetings (the first and second meetings for the learning process and the third meeting for social studies learning outcome assessment activities) and cycle II was also carried out 3 meetings. The two cycles were carried out for 2 months plus summarizing all existing research results. The results of the study show that the use of Canva and Wordwall-based learning media can improve student learning outcomes in social studies learning in class VI UPT SD Negeri 74 Bontorita II, Takalar Regency. This is evidenced by the increase in the average percentage of student learning outcomes in each cycle. In the first cycle, the average student learning outcome was 66 with a learning completion percentage of only 52%. In cycle II, there was a significant increase with the average student learning outcome of 82 with the percentage of learning completion reaching 91%. This means that the average percentage of student learning outcomes has exceeded the set success criteria of 75%.